How large are hysteresis effects? Estimates from a Keynesian growth model - Steven M. Fazzari; Alejandro González (Hans-Böckler-Stiftung, Macroeconomic Policy Institute (IMK), Forum for Macroeconomics and Macroeconomic Policies (FMM), 2023)
This paper estimates a demand-led model of macroeconomic growth and fluctuations in which the growth rate of the economy's supply side converges to the growth rate of demand. Convergence happens because labor supply and productivity growth respond to the degree of slack in the economy. Faster demand growth reduces slack and stimulates supply (and vice-versa). We estimate the model using simulated method of moments and find statistically significant and quantitatively important hysteresis effects: the semi-elasticity of productivity and labor supply to the unemployment rate are 0.73 and 0.26, respectively. For an economy with labor market slack, these estimates imply that supply growth could accommodate a one percentage point increase in the growth rate of demand with a reasonable 0.75 percentage point reduction in the long-run unemployment rate. Additionally, we show the model replicates major features of business cycles as well the response of the economy to autonomous demand shocks, providing further validation of this approach to understanding macroeconomic dynamics.
Keywords: E32; E12; O41; 330; Hysteresis; Demand-Led Growth; Supermultiplier